1995
DOI: 10.1042/bj3110183
|View full text |Cite
|
Sign up to set email alerts
|

Triplex-DNA stabilization by hydralazine and the presence of anti-(triplex DNA) antibodies in patients treated with hydralazine

Abstract: Hydralazine is an antihypertensive drug that elicits andti-nuclear antibodies in patients as an adverse effect. We investigated the ability of hydralazine to promote/stabilize the triplex DNA form of poly(dA).2poly(dT). Under conditions of low ionic strength, the polynucleotide melted as a double helix with a melting temperature (Tm) of 55.3 degrees C. Hydralazine destabilized this duplex form by reducing its Tm to 52.5 degrees C. Spermidine (2.5 microM), a natural polyamine, provoked the triplex form of poly(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 44 publications
(59 reference statements)
2
5
0
Order By: Relevance
“…In the absence of spermidine, the CD spectrum of poly(dA).2poly(dT) had a negative band at 250 nm and three positive bands at 220, 260 and 280 nm. These spectral features are similar to that previously reported for the duplex form of this polynucleotide [15,16,27]. In the presence of low concentrations of spermidine, triplex formation was indicated by an inversion of the positive peak centred at 220 nm with a new negative peak at 210 nm (inset).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…In the absence of spermidine, the CD spectrum of poly(dA).2poly(dT) had a negative band at 250 nm and three positive bands at 220, 260 and 280 nm. These spectral features are similar to that previously reported for the duplex form of this polynucleotide [15,16,27]. In the presence of low concentrations of spermidine, triplex formation was indicated by an inversion of the positive peak centred at 220 nm with a new negative peak at 210 nm (inset).…”
Section: Resultssupporting
confidence: 87%
“…These data demonstrate that the triplex form of poly(dA).-2poly(dT) is conformationally ultrapolymorphic and assumes a variety of conformations in the presence of spermidine. There was no major conformational alteration in the CD spectrum of poly(dA).poly(dT) duplex in the presence of spermidine under the same buffer conditions as used in the present study [27].…”
Section: Resultssupporting
confidence: 59%
“…Antibodies have the ability to recognize a specific molecule with high affinity. Although nucleic acids are often times weakly immunogenic, several antibodies against triple helices have been reported in the literature, including one that can discriminate between poly(U•A‐U) versus poly(U•dA‐dT) triple helices (Rainen & Stollar, 1977; Stollar & Raso, 1974; Thomas, Seibold, Adams, & Hess, 1995). Therefore, a straightforward approach to map RNA triple helices would be to perform an immunopurification using an anti‐RNA triple helix antibody followed by deep sequencing to identify bound nucleic acids.…”
Section: Discovering Rna Triple Helicesmentioning
confidence: 99%
“…It is suggested that these modified bases are antigenic and are responsible for lupus [34]. Hydralazine has been shown to intercalate into DNA [35, 36] and stabilize triplex-DNA in the presence of Mg 2+ and sperimidine. Interestingly, this triplex-DNA elicited an immunological response, and patients contained antibodies that reacted with this unusual form of DNA [36].…”
Section: Hydralazinementioning
confidence: 99%
“…Hydralazine has been shown to intercalate into DNA [35, 36] and stabilize triplex-DNA in the presence of Mg 2+ and sperimidine. Interestingly, this triplex-DNA elicited an immunological response, and patients contained antibodies that reacted with this unusual form of DNA [36]. Therefore, it is suggested that formation of antibodies to such triplex DNA may, in part, be responsible for lupus formation.…”
Section: Hydralazinementioning
confidence: 99%